Faktor Pemilihan Lokasi Bermukim pada Kawasan Rawan Bencana Longsor di Desa Guntur Macan, Kabupaten Lombok Barat - Baiq Harly Widayanti; Ardi Yuniarman; Febrita Susanti (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2018)
The purpose of this research is to understand the settlement pattern and the factors that determine the selection of settlement locations on areas prone to landslides at Guntur Macan Village, West Lombok Regency. The research uses qualitative method by conducting questionnaire and in-depth interview to respondents. Mapping of community houses together with analysis on nearest neighbors in viewing the settlement patterns were conducted. Categorical frequency analysis was used to measure villagers’ perceptions that affect their choice to settle at disaster-prone areas. The result of mapping shows the existing settlement patterns are either cluster, linear or spread. The result of analysis of nearest neighbors shows T value of 1.74, which means an evenly spread pattern. Based on villager’s perception, factors determining the selection of settlement locations on areas prone to landslides are distance away from high-noises, pollution levels that do not interfere with health, and accessibility to job sites.